Análisis financiero en la Farmacia Cruz Azul cantón Guayaquil, Parroquia Tarqui, Barrio Mapasingue en los periodos 2019-2020 - Zarate Zambrano, Domenica Lorena (2021)
The Financial Analysis case study in the Cruz Azul Pharmacy, Guayaquil Canton, Tarqui Parish, Mapaingue neighborhood, in the 2019-2020 periods. The economic activity carried out is the retail sale of a wide variety of products in stores was carried out at the Cruz Azul Pharmacy in the city of Guayaquil. Great success within the national territory, it has a large number of franchises in the four regions of the country. The objective of this project is to determine the current economic and financial situation of the Cruz Azul Pharmacy since a financial analysis will be carried out in the 2019-2020 periods to provide current information on the organization to detect difficulties that lead to future risks for the entity. The health crisis that occurred in the period of 2020 caused that the sales of the pharmacies increased and that during this period the stock of essential products such as alcohol, vitamins, paracetamol, masks among other products that were used is depleted. To health.